[artículo retractado/retracted article]:bycatch of helicops angulatus (linnaeus 1758) (reptilia: squamata: colubridae) in hoop-traps used to capture fresh water turtles on the coast of pará, brazil (2014)
ABSTRACT Between September, 2007, and August, 2009, six field excursions were conducted on the northern Brazilian coast (Romana and Maiandeua islands, state of Pará) for the collection of specimens of freshwater turtles (Rhinoclemmys punctularia and Kinosternon scorpioides) in natural ponds. Hoop-nets were used and 35 specimens of brown-banded water snakes, Helicops angulatus, were captured as bycatch in the traps. Thus, in addition to turtles, the procedure may be useful for the sampling populations of aquatic snakes. RESUMEN Entre septiembre de 2007 y agosto de 2009, seis excursiones de campo se llevaron a cabo en la costa norte de Brasil (islas Romana y Maiandeua, estado de Pará) para la recolección de especímenes de tortugas de agua dulce (Rhinoclemmys punctularia y Kinosternon scorpioides) en posos naturales. Utilizamos trampas en embudo. 35 ejemplares de la serpiente acuática Helicops angulatus, fueron capturados como pesca incidental en las trampas. Por lo tanto, además de las tortugas, el procedimiento puede ser útil para la toma de muestras de las poblaciones de serpientes acuáticas.